Komunikasi Antarpribadi Guru Bimbingan Konseling dalam Menangani Pelanggaran Kedisiplinan Santri di Pesantren Ar Raudlatul Hasanah Medan - Utami, Rizkika (unprimdn.ac.id, 2024)
This study aimed to analyze the interpersonal communication of counseling guidance teachers in handling violations of santri discipline at the Ar Raudlatul Hasanah boarding school in Medan. This research uses qualitative methods and case studies. The research subjects were two counseling guidance teachers, the primary informants; two ustadz, who were supporting informants; and a nurturing field teacher, who were research data triangulation informants. Data collection was done through in-depth interviews and observation. The results showed that interpersonal communication established in handling violations of Santri discipline is preventive communication. It provides direct action through reprimands and repressive communication, namely the threat of sanctions if in-disciplinary Santri continues to repeat its mistakes. Sanctions are given by counseling guidance teachers in dealing with violations of Santri discipline by prioritizing family use, which is a form of punishment without elements of violence and contains elements of understanding of religious knowledge. It is intended that disciplinary students can control their behavior.